Perancangan Sistem Informasi Pengelolaan Arsip Berkas Klaim Di Kantor BPJS Kesehatan Cabang Soreang - Derty Dorma Melania Nababan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Archives as a source of information play an important role in an institution. Archive management always evolves to keep up with the times with increasing numbers, without adequate maintenance, this can make retrieving archives very difficult. Management of claims file archives at the Soreang branch of the Health BPJS Office has not been effective. Based on the existing problems, an information system for managing claims file archives is needed as archive storage with computer technology, recording borrowing and returning files. Data collection methods include interviews, observation, and reading literature as well as application development with a structured waterfall in building a software. Making use of the an information system for managing claims file archives results in more effective performance using PHPRad Classic and MySQL software which is run using a web browser and XAMPP server in the form of Apache.